2017
DOI: 10.1161/circgenetics.116.001573
|View full text |Cite
|
Sign up to set email alerts
|

Application of Whole Exome Sequencing in the Clinical Diagnosis and Management of Inherited Cardiovascular Diseases in Adults

Abstract: Background With the advent of high throughput sequencing, the identification of genetic causes of cardiovascular disease (CVD) has become an integral part of medical diagnosis and management and at the forefront of personalized medicine in this field. The utility of whole exome sequencing (WES) for clinical diagnosis, risk stratification and management of inherited CVD has not been previously evaluated. Methods and Results We analyzed the results of WES in first two hundred adult patients with inherited CVD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 40 publications
3
33
3
Order By: Relevance
“…Siedelmann et al. reported that diagnosis was reached in 26.5% of patients (53 of 200 patients) who had familial cardiovascular disease at statistically higher rate than in our study ( p = .024 by Fisher's Exact test) (Seidelmann et al., ). Consistent with this, in their cohort of patients from families with multiple affected family members with CHD, Jia et al.…”
Section: Discussioncontrasting
confidence: 58%
“…Siedelmann et al. reported that diagnosis was reached in 26.5% of patients (53 of 200 patients) who had familial cardiovascular disease at statistically higher rate than in our study ( p = .024 by Fisher's Exact test) (Seidelmann et al., ). Consistent with this, in their cohort of patients from families with multiple affected family members with CHD, Jia et al.…”
Section: Discussioncontrasting
confidence: 58%
“…Seidelmann et al 41 reported their experience with WES in a variety of inherited cardiovascular conditions, including HCM. In 28 HCM patients, 13/28 (46.4%) had pathogenic or likely pathogenic variants identified; twelve occurred in genes found on current cardiomyopathy panels.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the vast majority of these studies have been performed in pediatric populations and in cancer patients. Hence, the value of WES in the diagnosis and management of adult patients with nononcological diseases is only recently emerging . In fact, in adult hepatology clinic, Wilson's disease, hemochromatosis, and alpha‐1 antitrypsin deficiency are routinely investigated as part of a comprehensive work‐up for liver test abnormalities and/or advanced liver disease by using single gene and/or gene panel test(s).…”
Section: Where Could Hepatologists Be Missing Liver‐related Genetic Tmentioning
confidence: 99%